Entrepreneurial Technology Resilience Mediates Entrepreneurial Marketing on Business Performance in Batik MSMEs - Wahdiniwaty, Rahma; Pranata, Sudadi; Komara, Nandang (Aptisi Transactions On Technopreneurship (ATT), 2025)
In the digital transformation era, technological resilience has become essential for Micro, Small, and Medium Enterprises (MSMEs), including Indonesia’s Batik industry, which must integrate technology to maintain competitiveness. However, many Batik MSMEs still face limited adoption of digital tools, resulting in declining performance and market reach. This study aims to analyze how entrepreneurial technology resilience mediates the relationship between entrepreneurial marketing and business performance in Batik MSMEs. A quantitative approach was used by distributing structured questionnaires to 383 Batik MSME owners in Indonesia. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate measurement validity and test hypotheses among three constructs, entrepreneurial marketing, entrepreneurial technology resilience, and business performance. Findings reveal that entrepreneurial marketing significantly influences both entrepreneurial technology resilience and business performance. Furthermore, entrepreneurial technology resilience also positively affects business performance and partially mediates the relationship between entrepreneurial marketing and business performance, explaining 80.2% of the variance in the model. The results confirm that technological resilience is a crucial mechanism that strengthens the effectiveness of entrepreneurial marketing strategies. Strengthening digital capabilities and adaptive innovation allows Batik MSMEs to enhance operational efficiency, market expansion, and overall performance. Therefore, improving technological resilience should be prioritized as a strategic policy for sustaining the Batik industry’s competitiveness.